Evaluation of physical activity status, anthropometric measurement and healthy lifestyle of women aged 20-45 years who applied to a private nutrition clinic - Süslü, Muge Seren; Perçinci, Nazal Bardak (Utan Kayu Publishing, 2023)
Objective: The aim of this study was to evaluate the obesity, physical activity status and healthy lifestyles of women aged 20-45 years who applied to a private nutrition clinic. Method: The study was carried out among 79 women aged 20-45 years who applied to a private clinic in Mersin. Participants were asked to complete questionnaires in order to examine data related to their daily physical activities and lifestyles. The researcher filled out questionnaires face to face and in the form of question and answer. One-way analysis of variance and t-test results were evaluated by frequency analysis method. Results: In our study, the mean total score was found to be 123.4 according to SESL II. 93.7% of the participants had inactive physical activity level, 2.5% had minimal physical activity level and 3.8% had very active physical activity level. Conclusion: In our study, healthy lifestyle behaviors of the participants were in average levels. It was found. This should be improved and the effects of lifestyle behaviors on health should be explained.